2017
DOI: 10.1371/journal.pone.0186764
|View full text |Cite
|
Sign up to set email alerts
|

Production of proinflammatory mediators in activated microglia is synergistically regulated by Notch-1, glycogen synthase kinase (GSK-3β) and NF-κB/p65 signalling

Abstract: Microglia activation and associated inflammatory response are involved in the pathogenesis of different neurodegenerative diseases. We have reported that Notch-1 and NF-κB/p65 signalling pathways operate in synergy in regulating the production of proinflammatory mediators in activated microglia. In the latter, there is also evidence by others that glycogen synthase kinase 3β (GSK-3β) mediates the release of proinflammatory cytokines but the interrelationships between the three signalling pathways have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 33 publications
3
31
0
Order By: Relevance
“…Pro‐inflammatory microglia are generally identified by expression of pro‐inflammatory cytokines and chemokines, such as tumor necrosis factor α (TNFα), interleukin‐6 (IL6), IL‐1β, and nitric oxide, while anti‐inflammatory‐polarized microglia identified by high expression of Arginase‐1 (Arg1), Interleukin‐4 (IL4), and CD206 (Hirbec et al, ; Parisi et al, ). Treatment with endotoxin LPS, amyloid beta peptide (Aβ), and other agents lead to pro‐inflammatory polarization, whereas treatment with anti‐inflammatory agents, such as IL4 and glatiramer acetate, result in anti‐inflammatory polarization (Cao, Karthikeyan, Dheen, Kaur, & Ling, ; Lee et al, ; McGeer & McGeer, ; Minett et al, ). However, many aspects of the microglia biology, especially the intrinsic molecular mechanisms leading to different activation states and their corresponding effect on cellular and neuronal function in different pathophysiological context, remain elusive and demand further investigation (Cherry, Olschowka, & O'Banion, ; McGeer & McGeer, ; Minett et al, ; Moller, Contos, Musante, Chun, & Ransom, ; Ramesh, MacLean, & Philipp, ; Wang, Tan, Yu, & Tan, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pro‐inflammatory microglia are generally identified by expression of pro‐inflammatory cytokines and chemokines, such as tumor necrosis factor α (TNFα), interleukin‐6 (IL6), IL‐1β, and nitric oxide, while anti‐inflammatory‐polarized microglia identified by high expression of Arginase‐1 (Arg1), Interleukin‐4 (IL4), and CD206 (Hirbec et al, ; Parisi et al, ). Treatment with endotoxin LPS, amyloid beta peptide (Aβ), and other agents lead to pro‐inflammatory polarization, whereas treatment with anti‐inflammatory agents, such as IL4 and glatiramer acetate, result in anti‐inflammatory polarization (Cao, Karthikeyan, Dheen, Kaur, & Ling, ; Lee et al, ; McGeer & McGeer, ; Minett et al, ). However, many aspects of the microglia biology, especially the intrinsic molecular mechanisms leading to different activation states and their corresponding effect on cellular and neuronal function in different pathophysiological context, remain elusive and demand further investigation (Cherry, Olschowka, & O'Banion, ; McGeer & McGeer, ; Minett et al, ; Moller, Contos, Musante, Chun, & Ransom, ; Ramesh, MacLean, & Philipp, ; Wang, Tan, Yu, & Tan, ).…”
Section: Introductionmentioning
confidence: 99%
“…polarization (Cao, Karthikeyan, Dheen, Kaur, & Ling, 2017;Lee et al, 2008;McGeer & McGeer, 2002;Minett et al, 2016). However, many aspects of the microglia biology, especially the intrinsic molecular mechanisms leading to different activation states and their corresponding effect on cellular and neuronal function in different pathophysiological context, remain elusive and demand further investigation (Cherry, Olschowka, & O'Banion, 2014;McGeer & McGeer, 2002;Minett et al, 2016;Moller, Contos, Musante, Chun, & Ransom, 2001;Ramesh, MacLean, & Philipp, 2013;.…”
mentioning
confidence: 99%
“…In 7 Mediators of Inflammation particular, we highlighted the induction of proinflammatory messengers mentioned above (TNF-α, IL-1β, NO, and NF-κB) [5]. Nevertheless, addition of Triticum vulgare extract (TVE), in combination with LPS showed an antiinflammatory action on specific markers of inflammation, restoring cytoplasmic levels of p65 and reducing its nuclear expression [5]; this type of mechanism has been reported by other works, in which the p65 restoration (reduction of nuclear staining of p65) is well considered an antiinflammatory signal [11,[27][28][29][30][31][32]. However, no other markers have been associated with "early inflammatory molecule" concept, except the four markers mentioned above.…”
Section: Resultsmentioning
confidence: 80%
“…Looking at the literature regarding the in vitro model simulating the molecular inflammatory mechanism, BV-2 cells [5,9,11,18]. Previously, we demonstrated that this cell culture system modulated inflammatory mediators, such as tumor necrosis factoralpha (TNF-α), interleukin 1beta (IL-1β), nitric oxide (NO), and nuclear factor kappa beta (NF-κB), after LPS stimuli [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation